The relationship of knowledge, parenting and economy in stunting prevention - Mochammad Alwan Dhiyak Ulkhak; Nova Kurniatsnaini (Institute of Computer Science (IOCS), 2023)
Stunting is a serious public health problem, especially in developing countries, including Indonesia. This study aims to examine the relationship between parental knowledge, parenting patterns, and economic conditions in efforts to prevent stunting in children. The results showed a significant correlation between parental knowledge about nutrition and healthy parenting practices. Parents with better knowledge tend to practice better parenting, such as providing nutritious food and better health care for their children. In addition, family economics also plays an important role in stunting prevention. Families with stable economic conditions have better access to quality food and health services necessary for optimal child growth and development. This study underscores the importance of education and counselling to parents on nutrition and healthy parenting as the first step in stunting prevention. In addition, efforts to improve families' access to economic resources are also needed to address this stunting issue. Awareness, education and social support are important factors in ensuring that children grow well and avoid stunting.